Assessment of landslide hazard models in Chamsangar basin - siamak baharvand; salman soori (تحقیقات کاربردی علوم جغرافیایی)
Landslide mapping is one of the approaches (which can be) used to define the slope stable critical areas and the maps prepared based on this demarcating are used in desining sustainable development. The purpose of this study is to compare the landslide susceptibility mapping models based on Fuzzy logic, Information value and area Density applied in the Chamsangar watershed. According to the tectonic and Iran old basins divisions, this basin is a part of folded Zagros. To study the stability of slopes in the Chamsang field, in first step the sliding point and subsequent distribution maps of landslide were prepared using satellite images and field visits (recording the sliding points by GPS). in this study, Landslide-related factors such slope, aspect, altitude, lithology, rainfall, landuse and distance from the road and drainage used in the landslide susceptibility analyses. To assess and classify was there models outputs the Sum of Quality (QS) index used. Results show that area Density model with QS=1.85 is the more suitable than Information value model with QS=1.60 and Fuzzy logic with QS=0.554 based on the out put of the area Density model, the 36.31, 44.78, 16.62, 1.65, and 0.63 percent of the area is located in very low, low, medium, high and very high risk classes, respectively.